2019
DOI: 10.1111/jasp.12564
|View full text |Cite
|
Sign up to set email alerts
|

Is disability really an obstacle to success? Impact of a disability simulation on motivation and performance

Abstract: In Western societies, statistics on the integration of people with disabilities into the labor market consistently indicate that this category of workers faces serious discrimination. Research has evidenced negative perceptions about their occupational skills, despite positive beliefs about their personal qualities. The main purpose of this study was to show how these subjective beliefs about disability can shape performance (speed and accuracy, Studies 1, 3, and 4) and self‐reported motivation (Studies 2, 3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
6
0
2
Order By: Relevance
“…The relationship between coping and performance is well-established (Tummers, 2016). For individuals with mental health conditions, it has been found that their negative self-image (Soeker et al, 2019), dysfunctional career expectancies, not seeking accommodations that help them perform (Kulkarni and Gopakumar, 2014), and the negative beliefs about the occupational skills of disabled individuals (Cohen et al, 2018) all negatively affect their job performance. Similarly, the stigma attached to mental health conditions negatively affects school performance (Talebi et al, 2016).…”
Section: Job Performancementioning
confidence: 99%
“…The relationship between coping and performance is well-established (Tummers, 2016). For individuals with mental health conditions, it has been found that their negative self-image (Soeker et al, 2019), dysfunctional career expectancies, not seeking accommodations that help them perform (Kulkarni and Gopakumar, 2014), and the negative beliefs about the occupational skills of disabled individuals (Cohen et al, 2018) all negatively affect their job performance. Similarly, the stigma attached to mental health conditions negatively affects school performance (Talebi et al, 2016).…”
Section: Job Performancementioning
confidence: 99%
“…Previous research has focused on “disability simulations” from an educational perspective and pedagogical perspective (Burgstahler and Doe, 2004; Barney, 2012; Shakespeare and Kleine, 2013; Leo, 2016; Leo and Goodwin, 2016; Cohen et al , 2019). In Sweden, insight simulation has also been described on the basis of learning and pedagogic (Borg et al , 1999; Herbert, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is through their work that they transform society and make history, it is an essential category to explain the world and society, the past and the future, in a practice that transforms humans, taking on the task of building a new society (Clot, 2017). Work is part of people's lives, whether for its emotional value, accomplishment of life goals, or just for "survival", having a subjective meaning for each one (Cohen et al, 2019;Salvador-Ferrer, 2020). This meaning is influenced by the way the inclusion of the individual takes place.…”
mentioning
confidence: 99%
“…According to research carried out by Carvalho-Freitas (2009), there is still a belief among managers in the need to separate PWD, whether in specific sectors or specialized companies (Cohen et al, 2019). The individual must adapt to the environment, while companies sometimes do not understand the importance of the adaptation of the workplace.…”
mentioning
confidence: 99%